The uses of Anglo-Saxon manuscripts, c. 1066-1200 - Faulkner, M; Mark Faulkner (2008)
This thesis examines the uses of Anglo-Saxon manuscripts in the 150 years immediately following the Norman Conquest. By focusing on the most common types of use evident in the manuscripts, it explores how readers actually interacted with books. It also treats manuscripts as cultural artefacts through which it is possible to observe the literary and social consequences of the Conquest. The Introduction summarises our current understanding of the literary culture of this transitional period. Chapter II, ‘Destruction and Conservation’, examines claims that Norman elites destroyed Anglo-Saxon manuscripts; finding these claims unjustified, it investigates the circumstances in which manuscripts were lost and identifies how readers evaluated the contents of pre-Conquest books. Chapter III, ‘The Movement of Pre-Conquest Manuscripts’, looks at the consequent loan, exchange and sale of pre-Conquest manuscripts after 1066. Chapter IV, ‘Updating Pre-Conquest Manuscripts’, discusses difficulties which Norman readers encountered with pre-Conquest books, including script, abbreviation, orthography and textual redaction, and examines how these technical features could be modernised. It also investigates more practical modernisations to liturgical books, chronicles and cartularies. Chapter V, ‘Glossing and Annotating’, concerns readers’ reactions to the texts found in pre-Conquest manuscripts, particularly vernacular homilies and translations. It argues that the post-Conquest classroom was essentially trilingual, though Latin became the lingua franca. Chapter VI, ‘Record-Keeping in Pre-Conquest Manuscripts’, explores the use of pre-Conquest manuscripts – copies of the gospels, liturgical books and patristic texts – as repositories for records. Chapter VII, ‘The Veneration of Pre-Conquest Manuscripts’, continues this exploration of the symbolic capital of pre-Conquest books by examining how Norman churchmen supported the veneration of particular manuscripts as secondary relics, and introduced new traditions regarding other books. The Conclusion refocuses the findings of this thesis on two key issues: early medieval reading practices and English literature between 1066 and 1200.